Surgical Treatment Methods of Post-coarctation Aneurysms of Aorta - I. M. Kravchenko; V. I. Kravchenko; Yu. Tarasenko; B. V. Cherpak; S. G. Klymenko; V. V. Lazoryshynets (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. Aortal coarctation is one of the most studied conditions of heart congenital defects, which comprises from 7% to 10% of all congenital heart defects.During many years the various treatment strategies were used. Open surgical reconstructive intervention was first de-scribed in 1945, and this was, as a rule, resection of aortal narrowed portion.Although the treatment of coarctation is usually successful in a short-term perspective, there is a well-known fact of de-velopment of complications at the later stages, especially after surgical reconstruction, such as post-coarctation aneurysms.Objective. To analyze surgical methods of correction of coarctation.Materials and methods.in the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine during the period 1960–2017, 4245 patients were operated with native coarctation of aorta.Selective patients’ choice for this work was restricted only by such cases of aneurysm of descending aorta, for which the data were reliable. Considering the above, we will be limited by the period of observation, starting from 1995.Totally, 91 cases with aneurysm of descending aorta were included in this work, 85 (93.4%) of patients were re-operated, 6 (6.6%) of patients were not operated due to various reasons. The patient distribution by age and gender at the moment of correction of aortal coarctation showed that they included 68 (74.7%) males and 23 (25.3%) females in the ratio 2.9:1. The average patient age by that time was 14.7, ranging from 1 to 38 years.By the moment of discovery of post-coarctation aneurysm the patients’ age increased to an average 38.1, ranging from 21 to 60 years. The average time interval between the surgery of aortal coarctation and diagnosis of aneurysm of descending aorta was 22 years, ranging from 1 month to 45 years.The frequency of complications of aneurysm of descending aorta after surgery of aortal coarctation was different for various surgical methods. Among the aneurysms, which developed after coarctation correction, the most frequent were aneurysms after implantation of synthetic patch – 61(88.5%). The less frequent were aneurysms in 6 (8.7%) patients after implantation of tubular prostheses, and in 2 (2.8%) patients – after end-to-end anastomosis.Results and discussion. Till recent time the standard treatment practice was open surgical operation with direct access to proximal part of descending aorta by left-sided lateral.In our Department 85 surgical interventions were performed, including 69 surgeries by the traditional surgical method. From these patients, 7(10.1%) were operated two times, and 2(2.9%) – three times. In all 69(81.2%) cases, operated by open traditional surgical method, we performed vascular prosthesis implantation.Such operations require highly qualified anesthetic support with obligatory differential endobronchial intubation, cor-rection of disorders of respiratory and kidney functions, and compensation of present and possible blood loss [4]. Consider-ing high probability of uncontrolled hemorrhage at the stage of aneurysm mobilization, we installed temporary bypass graft – 75.3% or CPB pump – 24.7%, from ascending aorta or left atrium to descending aorta or femoral artery.Hospital mortality in this patient cohort was 5.9%.The use of endovascular treatment of thoracic aorta aneurysm increased considerably since Dake et al. in 1994 implanted the first stent-graft into thoracic aorta.In our Department, we performed 16(18.8%) of the procedures under general anesthesia with spinal drainage. For the patients, who require the covering of the zone of going of left subclavian artery or left common carotid artery, we perform extra-anatomic shunting 9(10.5%), or even subtotal debranching 2(0.2%), if there is no possibility to use individually pre-pared scalped stent-graft. The most common access is through common femoral artery by operative access 15(17.6%), or, more recently, by transcutaneous access 1(1.1%).